(untitled) (London Journal of Research In Humanities and Social Sciences, 2026)
The participatory action research strategy based on community involvement (PAR) involved 65 incoming nutrition students at the National University of Entre Ríos and 7 graduating high school students with culinary arts degrees. The project was developed in an atypical course format in 2023, under the premise that “The Argentine food system must be changed, and young people can do it,” empowering them to become agents of sociocultural change. The city of Gualeguaychú, Argentina, and a public policy implemented within its territory, provided the context for this initiative. An initial awareness-raising effort among the students and outreach to local leaders, undertaken by the teaching team, allowed us to implement the strategy. This strategy was primarily developed outside the classroom, through ongoing interaction with others and using a dialogue methodology that was either spontaneous or initiated with key stakeholders in the local food system. The farmers’ markets and fairs in the town squares, showcasing local fruit and vegetable production as part of the municipal public policy, along with a recently opened community-run biopark on public land, provided the ideal setting for students to conduct research using primary sources and through unplanned conversations with consumers and/or producers. A raffle for a bag of freshly picked, seasonal vegetables, and the challenge of preparing meals to share with peers during each visit to the markets, allowed the young people to experience the organoleptic qualities of these vegetables firsthand. This motivated them to make dietary changes throughout the year and encouraged others to participate in the experience. The participatory action strategy between the two educational levels culminated in the Soup Festival at the university, where the convergence of knowledge was put to the test with a variety of colorful and flavorful soups.